Efficacy of subcutaneous interferon-beta in COVID-19: a meta-analysis and systematic review - Abuzar A. Asif (Taylor & Francis Group, 2021)
Type 1 interferons, especially interferon-beta, has been reported to be effective in COVID-19 patients in multiple randomized controlled trials. The aim of our meta-analysis and systematic review is to assess efficacy of subcutaneous IFN-beta in regards to mortality and discharge rate. Prospective, retrospective and randomized controlled trials were included. Primary outcomes measured were 28-day mortality and discharge rate. Secondary outcomes measured were mean hospital stay and post-intervention intubation rate. A thorough literature search was conducted in Medline, PubMed, Ovid journals, Google Scholar, and Cochrane Central Register of Controlled Trials & Database of Systematic Reviews from 1 April 2020 to 28 February 2021. Relative risk was calculated using both the Mantel–Haenszel method (fixed-effects model) and DerSimonian Laird method (random effects model). The heterogeneity among studies was tested using Cochran’s Q test, based upon inverse variance weights. 7 studies were included in the meta-analysis and systematic review. The IFN-beta group did not improve the 28-day mortality (RR = 1.276; 95% CI: 1.106–1.472, p = 0.001) or the discharge rate (RR = 0.906; 95% CI = 0.85–0.95, p = < 0.001). The mean hospital stay was 11.95± 2.5 days in the interferon-beta group and 11.43 ± 3.74 days in the traditional treatment group. Likewise, interferon-beta did not add any advantage to post-intervention intubation rate (RR = 0.92; 95% CI = 0.7841–1.0816, p = 0.3154). Our findings revealed that use of subcutaneous interferon-beta is futile in COVID-19.